A multifunctional region of the Shigella type 3 effector IpgB1 is important for secretion from bacteria and membrane targeting in eukaryotic cells. - Sonia C P Costa; Cammie F Lesser (PLoS ONE)
Type 3 secretion systems are complex nanomachines used by many Gram-negative bacteria to deliver tens of proteins (effectors) directly into host cells. Once delivered into host cells, effectors often target to specific cellular loci where they usurp host cell processes to their advantage. Here, using the yeast model system, we identify the membrane localization domain (MLD) of IpgB1, a stretch of 20 amino acids enriched for hydrophobic residues essential for the targeting of this effector to the plasma membrane. Embedded within these residues are ten that define the IpgB1 chaperone-binding domain for Spa15. As observed with dedicated class IA chaperones that mask hydrophobic MLDs, Spa15, a class IB chaperone, promotes IpgB1 stability by binding this hydrophobic region. However, despite being stable, an IpgB1 allele that lacks the MLD is not recognized as a secreted substrate. Similarly, deletion of the chaperone binding domains of IpgB1 and three additional Spa15-dependent effectors result in alleles that are no longer recognized as secreted substrates despite the presence of intact N-terminal secretion signal sequences. This is in contrast with MLD-containing effectors that bind class IA dedicated chaperones, as deletion of the MLD of these effectors alleviates the chaperone requirement for secretion. These observations indicate that at least for substrates of class IB chaperones, the chaperone-effector complex plays a major role in defining type 3 secreted proteins and highlight how a single region of an effector can play important roles both within prokaryotic and eukaryotic cells.